2015
DOI: 10.1590/s0104-64972015002317
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in population structure of the isopod Urobopyrus processae Richardson, 1904 (Isopoda: Bopyridae) infesting the branchial chamber of the night shrimp Ambidexter symmetricus Manning and Chace, 1971 (Decapoda: Processidae)

Abstract: Caridean shrimps are often infested by ectoparasites from the isopod family Bopyridae. Urobopyrus processae is a widespread species of bopyrid parasitizing the branchial (gill) chambers of members of the caridean family Processidae, including Ambidexter symmetricus. We examined hypotheses on differential infestation based on gender, castration of the host by the parasite, correlation between host and parasite size, and the fecundity of female parasites. Infestation rates varied from 1.3 to 32.1% between 2010 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
2
1
Order By: Relevance
“…mainly occurred in females of M. amazonicum . This is consistent with other studies conducted on carideans, in which parasite prevalence was found to be higher in females ( Chaplin-Ebanks & Curran, 2007 ; Rasch & Bauer, 2015 ; Barros et al, 2021 ) or equal for both sexes ( Marin Jarrin & Shanks, 2008 ). Although Pralon et al (2018) did not conclude that Probopyrus has sex-specific prevalence, due to the low number of parasites found in the specimens that they collected, our data suggest otherwise.…”
Section: Discussionsupporting
confidence: 93%
“…mainly occurred in females of M. amazonicum . This is consistent with other studies conducted on carideans, in which parasite prevalence was found to be higher in females ( Chaplin-Ebanks & Curran, 2007 ; Rasch & Bauer, 2015 ; Barros et al, 2021 ) or equal for both sexes ( Marin Jarrin & Shanks, 2008 ). Although Pralon et al (2018) did not conclude that Probopyrus has sex-specific prevalence, due to the low number of parasites found in the specimens that they collected, our data suggest otherwise.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, infestation by Probopyrus sp. occurred mostly in males of P. pandaliformis, differently from studies conducted on other carideans, in which parasite prevalence was either higher in female hosts (Chaplin-Ebanks and Curran, 2007;Rasch and Bauer, 2015) or equivalent for both sexes ( Jarrin and Shanks, 2008). With respect to P. northropi, it is not possible to conclude on its host sex-specific prevalence due to the low number of parasites found in the collected specimens.…”
Section: Resultscontrasting
confidence: 68%
“…) was also defined on a discrete subjective scale: 0=no embryos present, 1=embryos present and entirely comprised of yolk, 2=embryos present and blastodisc visible but no eyespot present, 3=embryos present with eyespots visible and cephalothorax and abdomen fused, 4=embryos present with cephalothorax and abdomen separated (Bauer , , ). Individuals with bopyrid isopod parasites ( Urobopyrus processae ), which castrate female A. symmetricus (Rasch & Bauer ), were not used in this study.…”
Section: Methodsmentioning
confidence: 99%